The Effects of Mango Mealy Bug (Rastrococcus onyadens) Infestation on Three Fruit Trees. (Journal of Science and Technology, 2015)
The Mango Mealy bug (Rastrococcus inadens) infestation has become a serious menace not only to Mango (Mangifera India) but also Sweet Orange (Citrus sinensis) and Breadfruit (Artocarpus alibis) production in the country. Studies carried out since 1984 have re/wiled that the infestation and ac-companying production of honey dew during the dry and the flowering seasons prevents effective flower pollination and fertilization thereby causing failure on fruit set and ultimate reduction in production. The few fruits produced may be rendered unattractive and unmarketable by the sooty mould colonies left on them In addition the heavy infestation of the under surface of leaves may also reduce leaf photosynthetic efficiency.